Abnormality in the Morphogenesis of Tooth Development and Relationship with Orthodontic Deformities and Treatment Approaches - Greta Roussanova Yordanova-Kostova; Mario Vaskov Grancharov; Gergana Diyanova Gurgurova (Hindawi Limited, 2021)
In the process of odontogenesis, a disturbance in the formation of the epithelium and mesenchyme can be observed and this can be manifested by atypical forms of dental development. Such biological phenomena with altered morphology are as follows: dens invaginatus (DI), dens evaginatus (DE), talon cusps, and double teeth (DT) or connate teeth (fusion and gemination). Patients with orthodontic anomalies who also exhibit teeth with morphogenetic disorders are presented in this article. Dens evaginatus and talon cusps pose orthodontic challenges in the treatment finishing phase. These reduce the possibility of achieving maximum intercuspidation between the lower and upper front teeth as well as poor incisor guidance. Other orthodontic challenges are as follows: the risk of occlusal trauma and periodontal loading of the antagonists and the possibility of accessory cusps to play the role of the inclined plane and lead to deviations in the closure of the lower jaw. The fused teeth can cause aesthetic and occlusal disturbances in the anterior segment. Furthermore, double teeth can lead to ectopic eruption or noneruption of adjacent teeth due to their increased crown size as is the case with one of the presented patients. This is because a double tooth occupies more space in the dental arch. If not diagnosed early, impaction of the adjacent tooth, violation of the occlusal ratios (Bolton/anterior), and exacerbation of the orthodontic deformity can be observed. The modern CBCT imaging is the best diagnostic method for identifying problems related to tooth positions or tooth germs.